Ἀληθὴς λόγος nas apologias de Justino Mártir - Neres, Gabriel Leite (2020)
Justin's clear intention in his Apologies is to placate the institutum neronianum, represented by the sentence christianos esse non licet. For this reason the document is conceived as a libellus, an instrument provided for in Roman law to reverse current jurisprudence. Its intention is to evoke the reason and philosophy of the roman imperial entourage, in spite of the evident semiotic clashes caused by the myth, rite and Christian ethos marked in the Roman Empire. The legal argument is mixed with the religious one, because the injustice is considered by the apologist as consequence of the influence of the demons, the corruption of λόγος per si. By evoking the ἀληθὴς λόγος (true Logos) he seeks to dissuade injustice and ungodliness imposed against Christians. The expression concerns the evidence of λόγος among men, both in the seminal and fragmented stage (λόγος σπερματικός), and integral and sufficient. The ἀληθὴς λόγος corresponds to “revelation”, expressing both its content and its author, i.e., Jesus Christ, the divine Logos. The philosophical problem derived from the assertion permeates the Apologies deeply, namely, how does “revelation” relate to the knowledge of the true or the good granted to men by God? The elucidation of the problem is circumscribed to the theses listed in chapter twenty-three of the First Apology. “Revelation” provides unequivocal knowledge of the truth, for (i) Christianity is the one, oldest, and truest teaching; it enables knowledge of God, for it attests that (ii) Jesus Christ is the first-born of God and master of men; it provides knowledge of the good while it dissuades men from legal, ethical, and religious misunderstandings caused by the influence of demons. Justin attests that (iii) revelation precedes incarnation, demons have corrupted it. The infusion of “revelation” is considered by the apologist to be a sufficient means of cushioning the institutum neronianum